2018
DOI: 10.3389/fmicb.2018.00361
|View full text |Cite
|
Sign up to set email alerts
|

ArgR of Streptomyces coelicolor Is a Pleiotropic Transcriptional Regulator: Effect on the Transcriptome, Antibiotic Production, and Differentiation in Liquid Cultures

Abstract: ArgR is a well-characterized transcriptional repressor controlling the expression of arginine and pyrimidine biosynthetic genes in bacteria. In this work, the biological role of Streptomyces coelicolor ArgR was analyzed by comparing the transcriptomes of S. coelicolor ΔargR and its parental strain, S. coelicolor M145, at five different times over a 66-h period. The effect of S. coelicolor ArgR was more widespread than that of the orthologous protein of Escherichia coli, affecting the expression of 1544 genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 76 publications
1
13
0
1
Order By: Relevance
“…A simple explanation could be that inner hyphae are lacking oxygen, and gas vesicles are formed in an attempt to find shallow waters with greater oxygen pressure. Another explanation is that gas vesicle proteins have a different role in a more generalized stress response, as has been previously suggested (Lee et al, 2005; Hesketh et al, 2011; Botas et al, 2018), in a process thus far unknown.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A simple explanation could be that inner hyphae are lacking oxygen, and gas vesicles are formed in an attempt to find shallow waters with greater oxygen pressure. Another explanation is that gas vesicle proteins have a different role in a more generalized stress response, as has been previously suggested (Lee et al, 2005; Hesketh et al, 2011; Botas et al, 2018), in a process thus far unknown.…”
Section: Discussionmentioning
confidence: 88%
“…Despite being widespread among actinobacteria, there are no reports of functional gas vesicles in these organisms (van Keulen et al, 2005). Transcriptional activation of this cluster has been seen in mutants of the arginine-synthesis regulator gene argR (Botas et al, 2018), of the nitrogen sensor glnK (Waldvogel et al, 2011), in response to saline stress, in a SigB dependent manner (Lee et al, 2005) and in the presence of antibiotics that target cell wall biosynthesis (Hesketh et al, 2011). These genes were greatly overexpressed in strain IB97, suggesting that their expression might be related to the general stress response shown by this strain.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that arginine metabolism plays an important role in antibiotic production and differentiation in Streptomyces spp. (26,27). However, the genes encoding arginine-degrading enzymes are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic and proteomic studies in Streptomyces have been made by different authors using distinct strains and conditions: (a) studying the sequential expression of genes at different times of growth (Botas et al, 2018 ; Fergusson et al, 2016 ); (b) comparing gene expression in different culture media (Hwang et al, 2019 ; Pinilla et al, 2019 ); (c) studying the wild-type strain in relation to particular mutants (Álvarez-Álvarez et al, 2014b , 2017 , 2018 ; Martínez-Burgo et al, 2015 , 2019 ; Pérez-Redondo et al, 2012 ), and (d) comparing the wild-type strain with industrial strains (Medema et al, 2011 ; Ünsaldi et al, 2017 ). Transcriptomic studies provide a wealth of information that frequently is difficult to interpret and will require years of research to understand the up- and downexpression of hundreds of genes reported in the different studies.…”
Section: Transcriptomic and Proteomic Studiesmentioning
confidence: 99%
“…Improved CA-producing strains have been obtained by increasing the glyceraldehyde-3-P pool through genetic engineering of the glycolytic pathway (Li & Townsend, 2006 ), by increasing the copy number of the glpK1D1 glycerol biosynthesis genes and by addition of glycerol to the cultures (Baños et al, 2009 ; Shin et al, 2021 ). The gene cluster for arginine and the arginine gene cluster regulation in Streptomyces have been thoroughly studied using genetic and transcriptomic tools and this might be useful to improve CA production (Botas et al, 2018 ; Pérez-Redondo et al, 2012 ; Rodríguez-García et al, 2000 ). The CA pathway starts with the condensation of glyceraldehyde-3-P and arginine by the carboxyethylarginine synthase (CeaS2), formation of a β-lactam ring by the β-lactam synthetase (Bls2), closing of the clavam ring by the multifunctional clavaminate synthase (Cas2), able to hydroxylate, cyclisise and desaturate its substrate in a single-binding cavity leading to the formation of (3S, 5S) clavaminic acid (Wojdyla & Borowski, 2021 ).…”
Section: Organisation Of the Genes Of Cephamycin C Clavulanic Acid An...mentioning
confidence: 99%